Efektivitas Pengelolaan UMKM Dengan Pendekatan 3 Pilar OPOP (Santripreneur, Pesantrenpreneur, Sociopreneur) di Sekitar Pondok Pesantren Darussalam Al-Faishliyah Sampang - Sa’adah, Nurus; Rahman, Taufiqur (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims as an effort to advance the Islamic boarding school economy through the management of MSMEs around the Islamic boarding school, it needs to be done to create a superior and competitive Islamic boarding school in creating quality graduates. The Darussalam Al-Faisholiyah Sampang Islamic boarding school in Indonesia serves as the study's primary site because of its major role in fostering the economic autonomy of Islamic boarding schools via the efficient application of MSMEs management grounded on the three pillars of the OPOP framework. Therefore, the research conducted by researchers aims to provide significant solutions through several references in managing MSMEs products and strengthening the economic independence of Islamic boarding schools, so that Islamic boarding schools across Indonesia, and not only Darussalam Al-Faisholiyah Sampang, may see the economic impact that Islamic boarding schools have on their students, their schools, their alumni, and Indonesian society as a whole. This study offers actionable solutions in the form of a process flow for achieving financial autonomy in Islamic boarding schools.